PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN LECTORA INSPIRE PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Sherli Pentianasari; Deni Adi Putra; Badruli Martati (Universitas Negeri Makassar, 2023)
This study aims to develop interactive learning media assisted by Lectora Inspire in science learning that are valid, practical, and effective. This research is a development research using the 4-D development model. This research was carried out at SD Muhammadiyah 2 Surabaya with the research subject being class IV which consisted of 24 students. The research instruments used were material and media validation questionnaires, teacher and student response questionnaires, as well as learning achievement tests. Data validation and questionnaire results were analyzed descriptively qualitatively. Based on the results of the research, learning media developed that have been tested and validated by material experts obtain an average of 97.66%, media experts obtain an average of 95.99%, so that the average validity of learning media is 96 .83%. Instructional media are also considered practical for use by teachers with a percentage obtained of 99% and the results of the percentage of practicality by students obtained by 93%. Learning media is also used effectively with the percentage of classical completeness obtained by 91.66%. From the results of the study, it can be concluded that the learning media developed obtained very valid, very practical, and very good criteria and were declared suitable for use in IPAS learning in elementary schools.